General chemistry : the essential concepts - Chang, Raymond (Dubuque : McGraw Hill Education, 2003)
This text aims to present the material that is essential for a one-year general chemistry course. The core topics of chemistry are addressed, and this third edition features new Spartan molecular models, animations correlated to the text, the addition of molecular orbital theory, and more.
Keywords: CHEMISTRY